2010
DOI: 10.1111/j.1558-5646.2009.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Rogers’ Paradox Recast and Resolved: Population Structure and the Evolution of Social Learning Strategies

Abstract: We explore the evolution of reliance on social and asocial learning using a spatially explicit stochastic model. Our analysis considers the relative merits of four evolved strategies, two pure strategies (asocial and social learning) and two conditional strategies (the "critical social learner," which learns asocially only when copying fails, and the "conditional social learner," which copies only when asocial learning fails). We find that spatial structure generates outcomes that do not always conform to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 25 publications
5
131
2
1
Order By: Relevance
“…It is like cheating on a test: you do as well as the person you copy from but avoid all that tedious studying. However, evolutionary models show that if this is the only benefit of social learning, there will be no increase in the ability of the population to adapt (31)(32)(33)(34). This surprising result emerges from the coevolutionary processes that affect the kinds of behaviors that are available to imitate and the psychology that controls learning and imitation.…”
Section: Cultural Adaptation Is a Population Processmentioning
confidence: 95%
“…It is like cheating on a test: you do as well as the person you copy from but avoid all that tedious studying. However, evolutionary models show that if this is the only benefit of social learning, there will be no increase in the ability of the population to adapt (31)(32)(33)(34). This surprising result emerges from the coevolutionary processes that affect the kinds of behaviors that are available to imitate and the psychology that controls learning and imitation.…”
Section: Cultural Adaptation Is a Population Processmentioning
confidence: 95%
“…These models include, but are not limited to, models of social learning (e.g., refs. [164][165][166][167], models of language evolution (e.g., refs. [168][169][170][171], empirically driven verbal models of human evolution based on patterns in material culture (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that the population is expected to reach an equilibrium at which individual and social learners will be equal in their fitness. Rendell et al [28] however showed that by adding a spatial structure to this problem the mixed equilibrium may not occur.…”
Section: Introductionmentioning
confidence: 99%